Nasal immunization with AMH-INH-RFRP DNA vaccine for improving follicle development and fertility in buffaloes - Chen, Chao; Zhao, Xuhong; An, Zhigao; Ahmad, Muhammad Jamil; Niu, Kaifeng; Zhang, Xinxin; Nie, Pei; Tang, Jiaomei; Liang, Aixin; Yang, Liguo (Frontiers in Endocrinology, 2023)
In this study, the effects of a novel AMH-INH-RFRP DNA vaccine on immune response and reproductive performance were investigated in buffalo. A total of 84 buffaloes were randomly divided into four groups and nasally immunized twice a day with 10 ml of either AMH-INH-RFRP DNA vaccines (3 × 1010 CFU/ml in group T1, n = 21, 3 × 109 CFU/ml in group T2, n = 21 and 3 × 108 CFU/ml in group T3, n = 21) or PBS (as a control, n = 21) for 3 days, respectively. All animals were boosted with an interval of 14 days. Antibody titers and positivity rates were then evaluated by ELISA assay. The results showed that both the primary and booster immunization significantly increased the anti-AMH, anti-INH, and anti-RFRP antibody titers in the T2 group compared with that in the T3 group (P < 0.05). After the primary immunization, the antibody positivity rate was significantly higher in the T2 group than that in the T3 group (P < 0.05). Subsequently, steroid hormones and cytokine levels in the serum of all experimental animals from the antibody-positive (P) and antibody-negative (N) groups were measured using ELISA kits. The results indicated that concentrations of E2, IFN-γ, and IL-4 were significantly higher in the P group compared to the N group (P < 0.01), whereas there was no significant difference in the P4 concentration (P > 0.05). Ultrasonography results revealed a highly significant increase of 2.02 mm in the diameter of ovulatory follicles in the P group compared to the N group (P < 0.01). In parallel, growth speed of dominant follicles was considerably higher in the P group than that in the N group (1.33 ± 1.30 vs 1.13 ± 0.12, P < 0.05). Compared to group N, the rates of oestrus, ovulation, and conception were also significantly higher in the P group (P < 0.05). Overall, the novel AMH-INH-RFRP DNA vaccine improves the proportion of oestrus, ovulation and conception in buffalo by promoting the production of E2 and the growth of follicles.